Westernization Crisis in Yukio Mishima’s “Patriotism” and H. Nihal Atsız’s Ruh Adam - Şeyma Karaca Küçük (Türkiyat Mecmuası)
The term modernization, which is used to refer to social, cultural, economic, and technological change and development in the context of the progressive experience of the west, brings along certain issues when examining the modernization process of non-western societies. Thus, it cannot adequately explain this experience. In fact, the modernization experienced by these societies has introduced an environment of cultural duality and crisis. In this regard, Japan and Turkey share similarities. Japanese and Turkish societies, which underwent the modernization process under the influence of the west and were described as non-western environments, were exposed to mental confusion and dilemma between traditional and western elements in an environment in which the west was idealized. This crisis can be observed in a short story by Japanese writer Yukio Mishima (1925–1970) entitled “Patriotism” (1961) and a novel by H.Nihal Atsız (1905–1975) entitled Ruh Adam (1972). In both works, when pursued alongside the policy of westernization, modernization has caused a chaotic environment with changing political, social, and cultural structures, which ultimately resulted in opposition to westernization. Mishima and Atsız also react to this change through their nationalist identities and reflect on these reactions through the characters they fictionalized. In this sense, the anti-westernization oppositions of the characters in these works are situated in a crisis environment that could even lead them to suicide. This study aims to compare how Yukio Mishima in “Patriotism” and H.Nihal Atsız in Ruh Adam depict the influence of modernization/ westernization on the characters and how the authors reflect their nationalist identities regarding the fact that a relationship exists between the personal lives of the writers and their works. Thus, it seeks to discuss the crisis environment experienced in the modernization of Japanese and Turkish societies, which are frequently referred to as non-western societies.